Narrativas de protesto: a copa das black blocs - Pinheiro Junior, Ari Leme (2016)
This dissertation is the result of empirical monitoring of political demonstrations where young people expressed through the Black Bloc tactic. It is a participant observer report. Seeks, in acts of street protests and social networking sites, how is the construction of knowledge and realities of these young people. Seeks to understand the political forces opposing the idea of autonomous organization that tracks youth social movements and collective action close to the fans of tactical Black Bloc. Analyzes the pages of Brazilian mass media, the dispute the meaning of the 2013-2014 protests among the ultra-liberal discourse, government supporters and revolutionaries. This research follows the steps of how was built the historical image of the Black Bloc in the national press and proposes a historical script to its spectacular appearance in Brazilian media in June 2013. The research seeks to understand the contemporary scene of street protests across narratives gathered in demonstrations against the FIFA World Cup 2014 and interviews marked the tactical fans in their living spaces. Part of this work an audiovisual documentary, edited with scenes observed in fieldwork.